2018
DOI: 10.1002/etc.4040
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of organophosphorus flame retardants/plasticizers and synthetic musks in sediments from source water in the Pearl River Delta, China

Abstract: The Pearl River (China) and its tributaries receive discharges of treated/untreated domestic sewage and industrial wastewater throughout the entire drainage basin. The river provides source water for many local inhabitants, and there is great concern over its pollution status. Fifteen sediment samples were collected from source water areas in the Pearl River Delta, and analyzed for the occurrence and distribution of 2 classes of emerging pollutants, organophosphorus flame retardants (OPs) and synthetic musks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Using only stable isotope technology to analyze nitrogen sources may thus not be accurate. Something more stable and more relevant to life such as plasticizers could be used together with a stable nitrogen isotope to identify nitrogen from domestic wastewater [ 28 , 29 ]. Also, during the research, we found that the organic nitrogen content in the water is complex, and determining the composition of organic nitrogen would be one of the next research directions.…”
Section: Discussionmentioning
confidence: 99%
“…Using only stable isotope technology to analyze nitrogen sources may thus not be accurate. Something more stable and more relevant to life such as plasticizers could be used together with a stable nitrogen isotope to identify nitrogen from domestic wastewater [ 28 , 29 ]. Also, during the research, we found that the organic nitrogen content in the water is complex, and determining the composition of organic nitrogen would be one of the next research directions.…”
Section: Discussionmentioning
confidence: 99%
“…Tributyl phosphate (TBP), TPP, tri-m-cresyl phosphate (m-TCP) and TDCPP are the commonly detected OPFRs in the Pearl River Delta (PRD), which are also chosen as targets in this paper. The concentration of OPFRs in the PRD was as high as 72.6 ng.g −1 dw in sediments with the detection rate of 40% ~ 100% (Zeng et al 2018b). Rivers carry a large amount of land-based water and sediments from the land to the coastal ocean (Gong et al 2019), constituting the main source of OPFRs in the ocean (Lai et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…(He et al 2021). The PRD includes the mega city of Guangzhou, the famous electrical/electronic manufacturing base in Dongguang, and the manufacturing area specializing in the production of plastics, textiles and personal protective articles (Zeng et al 2018b). A study shows that the average concentration of Σ 4 OPFRs at all sites in soil in Guangzhou of the PRD region was as high as 97.3 ng.g −1 dw (Cui et al 2017).…”
Section: Concentration Of Opfrs In Sediment and Comparison To Previou...mentioning
confidence: 99%
See 2 more Smart Citations